What Will a PhD Look Like in the Future? Perspectives on Emerging Trends in Sustainability Doctoral Programs in a Time of Disruption. (December 2020) - Lazurko, Anita; Alamenciak, Tim; Hill, Lowine Stella; Muhl, Ella-Kari; Osei, Augustine Kwame; Pomezanski, Dorian; Schang, Kyle; Sharmin, Dilruba Fatima
In this perspective paper, we aim to provide insights that can help academic institutions and transdisciplinary doctoral programs position themselves within a changing research landscape and prepare for future disruption. We are a group of eight first-year, transdisciplinary doctoral students at the University of Waterloo, representing diverse disciplinary perspectives and gender and cultural experiences. In the process of orienting ourselves as sustainability researchers, we conducted collaborative workshops to critically examine our intellectual and disciplinary positionality by reflecting on the question: What will a PhD look like in the future? Amid this process, the coronavirus pandemic happened, causing a major disruption to our research activity and personal lives. What began as a reflective process on doctoral research shifted toward a more substantive and far reaching discussion about disruption and academia. Through our workshops we identified four emerging trends in the domain of sustainability scholarship that are shaping the future of the academic experience: shifts from disciplinarity to transdisciplinarity; researchers as knowledge holders to knowledge brokers; researcher competencies as bounded to boundary-less; and metrics of success as citation impact to societal impact. We also identified three broad trends in the context of academia that were accelerated by the coronavirus pandemic and may be exacerbated by future disruptions: (1) increasing virtualization of research and teaching; (2) increasing need for flexibility of academic structures and processes; and (3) growing economic and socio-political uncertainty. We offer concrete recommendations that encourage doctoral students and programs to play a more fundamental role in solving complex challenges in a disrupted academic and social landscape. We conclude with our vision of the PhD student of the future as one who thrives in transdisciplinary settings, links society and science through knowledge brokering, spans boundaries between multiple epistemologies to communicate and collaborate through uncertainty, and prioritizes societal impact.